Does silica addition affect translocation and leaching of cadmium and copper in soil?. (1st November 2021) - Stein, Mathias; Georgiadis, Anna; Ingwersen, Joachim; Rennert, Thilo
Abstract: Soil and groundwater contamination with potentially toxic elements (PTEs) including cadmium (Cd) and copper (Cu) has become a serious problem for ecosystem functioning. Silicon (Si) may precipitate these metals as silicates, and may also form, at undersaturation of silicates, 'Si-contaminant compounds', i.e. particles of polymerized silica with PTEs incorporated or adsorbed by inner-sphere complexes. While the formation of these compounds in aqueous solution has been proven, their formation in soil remains unclear yet. Therefore, we conducted column experiments with a topsoil horizon artificially contaminated with Cd or Cu solutions (10 mM) in the presence (10 mM) and absence of monomeric Si, and monitored the elemental composition of the eluates during 12 irrigation steps with artificial rainwater by microwave-plasma atomic emission spectrometry, the size and charge of the particles eluted by dynamic light scattering and phase analysis light scattering, and determined the spatial distribution of total and exchangeable Cd and Cu in soil after the experiments. When Si was previously applied to soil, significantly larger particles (up to > 200 nm) in the eluates indicated Si polymerization and formation of Si-contaminant compounds. However, Cd and Cu concentrations were very low (<0.4 μM), pointing to efficient retardation in soil. In any variant, the particles formed were slightly negatively charged (−11 mV). The molar metal:Si ratios in the eluates and significant correlations between the amounts of Si and metals in soil extracted by NH4 NO3 pointed to the formation of Si-contaminant compounds, too. More Cu than Cd was retained in soil, and significantly more in the presence of Si, but less Cu than Cd was in exchangeable form. While particularly Cu formed Si-contaminant compounds, which reduced the concentration of Cu ions, the Si-contaminant-compound particles in the eluates remained very small, thus potentially susceptible to particulate export from soil into the groundwater. Graphical abstract: Image 1 Highlights: Silica addition to soil enhanced particulate transport of cadmium and copper in soil. Silica addition increased the total contents of copper in soil. Silica increased the contents of exchangeable cadmium and copper in soil. Copper formed more stable compounds than cadmium in the presence of silica. Abstract : Cadmium and copper form particulate Si-contaminant compounds during polymerization of silicic acid in soil, which may reduce metal mobility, particularly that of Cu.